Current and Past Immunodeficiency Are Associated With Higher Hospitalization Rates Among Persons on Virologically Suppressive Antiretroviral Therapy for up to 11 Years. (26th December 2020) - Davy-Mendez, Thibaut; Napravnik, Sonia; Eron, Joseph J; Cole, Stephen R; van Duin, David; Wohl, David A; Hogan, Brenna C; Althoff, Keri N; Gebo, Kelly A; Moore, Richard D; Silverberg, Michael J; Horberg, Michael A; et al.
Abstract: Background: Persons with human immunodeficiency virus (PWH) with persistently low CD4 counts despite efficacious antiretroviral therapy could have higher hospitalization risk. Methods: In 6 US and Canadian clinical cohorts, PWH with virologic suppression for ≥1 year in 2005–2015 were followed until virologic failure, loss to follow-up, death, or study end. Stratified by early (years 2–5) and long-term (years 6–11) suppression and lowest presuppression CD4 count <200 and ≥200 cells/µL, Poisson regression models estimated hospitalization incidence rate ratios (aIRRs) comparing patients by time-updated CD4 count category, adjusted for cohort, age, gender, calendar year, suppression duration, and lowest presuppression CD4 count. Results: The 6997 included patients (19 980 person-years) were 81% cisgender men and 40% white. Among patients with lowest presuppression CD4 count <200 cells/μL (44%), patients with current CD4 count 200–350 vs >500 cells/μL had aIRRs of 1.44 during early suppression (95% confidence interval [CI], 1.01–2.06), and 1.67 (95% CI, 1.03–2.72) during long-term suppression. Among patients with lowest presuppression CD4 count ≥200 (56%), patients with current CD4 351–500 vs >500 cells/μL had an aIRR of 1.22 (95% CI, .93–1.60) during early suppression and 2.09 (95% CI, 1.18–3.70) during long-term suppression. Conclusions: Virologically suppressed patients with lower CD4 counts experienced higher hospitalization rates and could potentially benefit from targeted clinical management strategies. Abstract : Among patients virologically suppressed on antiretroviral therapy for up to 11 years, those with CD4 counts ≤500 vs >500 cells/µL had higher hospitalization rates, including patients without a history of CD4 count <200 cells/µL prior to virologic suppression.